The Effectiveness of Virtual Learning in a Transformational Leadership Perspective - Suwatno Suwatno; Hady Siti Hadijah; A. Adman; Nani Imaniyati; Riske Faldesianti (Jurnal Ad'ministrare, 2022)
This study aimed to analyze the effect of Virtual Transformational Leadership and Student Creativity on the Effectiveness of Virtual Learning in several universities throughout the city of Bandung. Using surveys and quantitative approaches, the research was conducted on 200 students and 200 lecturers in Bandung. The data were analyzed descriptively with the PLS Structural Equation Model (Garson, 2018). It was found that Virtual Transformational Leadership and Student Creativity positively influence the Effectiveness of Virtual Learning in several universities throughout the city of Bandung. Thus, the transformational leadership style approach used by lecturers was sufficient to encourage the increase in the effectiveness of virtual learning, and the creativity possessed by students greatly encouraged the increase in the effectiveness of virtual learning. This research is expected to impact the implementation of learning in all educational units, which are converted into virtual learning, into an effective and efficient learning implementation amidst the limitations of the existing infrastructure.